Endometriosis-Associated Massive Ascites in an Asian Woman: A Case Report of a Rare Clinical Entity - Nuntasiri Eamudomkarn; Naratassapol Likitdee; Pilaiwan Kleebkaow; Chumnan Kietpeerakool (Hindawi Limited, 2020)
Massive ascites as a presentation of endometriosis is a rare clinical entity that is most commonly seen in black nulliparous females. Herein, we describe a case of a 32-year-old multiparous Thai woman who presented with a two-year history of abdominal distension. Computerized tomography of the abdominopelvic region showed an infiltrative enhancing lesion involving the cul-de-sac and perirectal region with massive loculated ascites, suggesting carcinomatosis peritonei. Abdominal paracentesis was performed to yield fluid samples for evaluation, which revealed no malignant cells, and polymerase chain reaction (PCR) was negative for tuberculosis. The patient underwent exploratory laparotomy which revealed a large amount of serosanguinous ascites, thickened matted bowel loops, and necrotic debris covering the entire surface of the peritoneum and visceral organs. The surgical procedures included drainage of 6.5 liters of ascites, lysis adhesion, biopsy of the peritoneum, and right salpingo-oophorectomy. Histologic examination revealed benign endometrial glands with stroma at the peritoneum tissue and broad ligament. Other causes of ascites were excluded. The ascites responded to drainage and hormonal suppression. A final diagnosis of endometriosis was made based on these findings. Endometriosis should therefore be considered in differential diagnosis in women of childbearing age who present with ascites.